BIOLOGICAL ACTIVITIES OF EXTRACTS OF PYCNANTHUS ANGOLENSIS (WELW.) WARB - Onocha, P.; Otunla, E. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Chloroform and methanolic extracts of the leaves, roots and stem of Pycnanthus angolensis (Myristicaceae) were investigated with the goal of establishing its acclaimed potency as an anthelmintic and antimicrobial agent. The result of the agar diffusion studies revealed that the leaf methanol extract caused inhibition against two of the 5 bacterial strains namely, Salmonella typhii and Pseudomonas aeruginosa used for the study. It also exhibited marked inhibition against the three fungal strains used for the study, the order of sensitivity being Aspergillus niger > Candida albicans > Dermatophyte sp. The chloroform extract of the leaves and the methanol extracts of the leaves and stem exhibited considerable anthelmintic activities in vitro using Fasciola gigantica, Taenia solium and Pheritima pasthuma. The sensitivity was concentration-related and comparable to that of the reference compound piperazine citrate. These results are consistent with the folklore use of the plant in treatment of helmintic and microbial infections. Acknowledgement: Senate Research Grant (SRG/FSC/2000/22A).